RE-DESIGN SISTEM KATEGORI PADA STARTUP WARSHOP DENGAN METODE USER CENTERED DESIGN - Antoinette, Cheriel Leily; Marlina; Mohammad Sofyan S. Thayf (KHARISMA Tech, 2025)
This study redesigns the category feature interface on the WarShop application using the user-centered design method to improve the user experience. The goal is to make it easier for users to find the products they want specifically and quickly. Data was obtained through interviews and observations of 10 WarShop users, where 9 users felt that the existing category features were not specific, causing users to take longer to find the products they wanted. The user-centered design method was chosen because it involves users from the beginning of the design process, resulting in a better interface that meets user needs. This interface design resulted in a more specific category feature that helps users find items directly according to the category they are looking for, and provides recommendations for similar products based on the product being searched for using keywords or the product being displayed. After the redesign, an evaluation was carried out using testing with the metrics task success, time on task, and error metrics with five users who had been previously interviewed, based on research indicating that the majority of usability issues can be found by the first five users tested. There were no problems found in the task success test and the error test resulted in an average error rate for all tasks of 0%, while in the time on task, some users exceeded the time limit. However, this is because users were interested in other products displayed based on category and recommendations.